Effects of Various Factors on the Viv-Induced Fatigue Damage In The Cable Of Submerged Floating Tunnel - Luoa Gang; Chen Jianxun; Zhou Xiaojun (Polish Maritime Research, 2015)
According to the modal superposition method, the vortex vibration procedure of submerged floating tunnel cable was compiled using Matlab, based on the calculated results, the fatigue damage was predicted. The effects of various factors, such as cable density, cable length, and pretension and velocity distribution on vortex induced fatigue damage in the cable were studied. The results show that velocity distribution has more effect on the cable fatigue damage than cable length, cable density and pre-tension. Secondly, cable length has also relatively effect on the cable damage fatigue, cable density and pretension has limited in a certain range.